Unveiling the Eris Subvariant: The Next Challenge in the COVID-19 Pandemic? - Kali, Arunava (Journal of Laboratory Physicians, 2023)
Since the COVID-19 pandemic's onset, the SARS-CoV-2 virus has displayed remarkable mutation abilities, resulting in distinct variants. Alpha, Beta, Gamma, Delta, and Omicron are major World Health Organization (WHO)-identified variants of concern. The Omicron variant and its sub-lineages dominated globally in 2022. A novel strain, EG.5.1 (Eris), originating from Omicron's XBB sub-lineage, has recently sparked a significant COVID-19 surge across continents. Detected since June 2023, EG.5.1 is linked to increased cases in Europe, the Americas, and Asia. Factors like waning immunity, overcrowding, and poor air quality contributed to its rise. This variant is likely to prevail over other circulating variants and become dominant in UK by September 2023. Surveillance of its global epidemiology and implementing preventive measures have become imperative in light of the current situation.
Keywords: EG.5.1; Eris subvariant; SARS-CoV-2